The first “Sustainable Finance Forum” organized by AFFI..... - BERTRAND, PR. PHILIPPE (Bankers, Markets & Investors, 2024)
The first “Sustainable Finance Forum” organized by AFFI was launched in 2022. It was born of two convictions: the need for regular dialogue between professionals and academics, and the urgent need to overhaul the theoretical frameworks and practices of responsible and sustainable finance. The second edition was held on December 15, 2023 and was attended by 130 people. Organized by AFFI, in partnership with Af2i and Amafi, it was supported by thirteen professional associations and financial institutions. As with the first edition, Bankers, Markets & Investors has decided to publish a special issue echoing the debates that took place during this day. Bankers, Markets & Investors aims to publish high-quality, relevant research that provides fresh insights into this evolving field, supporting practitioners in addressing these ongoing challenges. Hubert Rodarie, President of Af2i, introduced the morning session, stressing the importance of building bridges between practitioners and academics. Then, three panels discussed topics related to the most discussed items on the agenda of corporates, intermediaries and Investors. The first round table “Extra-financial reporting, ambitions and realities” was the corporate theme. The second “How do retail customers perceive financial and extra-financial issues?” was the round table devoted to intermediaries. Finally the last one “How can investors integrate climate risks?” was the Investors panel. Each panel was introduced by a scientific expert setting the context and summarizing the recent literature on the topic. The afternoon session was devoted to scientific papers dealing with sustainable finance from an angle specifically applied to practical problems. It began by a keynote speech by Sébastien Pouget on the influence of carbon emissions on the valuation of bonds issued by US companies. . Eighteen papers were presented and two of these contributions are presented in this BMI issue. They have been peer reviewed in the same way as classical articles. The first contribution, by Diana Pop, Caroline Marie-Jeanne and Régis Dumoulin, deals with willingness of investors to pay a higher price to invest in social projects. The second study written by Valentin Courquin demonstrates how risk management professionals can leverage currently available climate data to identify climate risks that have the most impact on their activity. The first “Focus On” by Philippe Dupuy, Caroline Marie-Jeanne and Nadège Ribau-Peltre is based on the introductory presentation of the second panel. The second “Focus On” by Jean-Laurent Viviani was the introduction of the first panel of the morning. I hope you enjoy reading this issue and would be thrilled to welcome your contributions to the future Sustainable Finance Forums.